2021
DOI: 10.1021/acs.est.1c00375
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oxidation of Organic Contaminants by Iron(II)-Activated Periodate: The Significance of High-Valent Iron–Oxo Species

Abstract: Potassium periodate (PI, KIO 4 ) was readily activated by Fe(II) under acidic conditions, resulting in the enhanced abatement of organic contaminants in 2 min, with the decay ratios of the selected pollutants even outnumbered those in the Fe(II)/ peroxymonosulfate and Fe(II)/peroxydisulfate processes under identical conditions. Both 18 O isotope labeling techniques using methyl phenyl sulfoxide (PMSO) as the substrate and Xray absorption near-edge structure spectroscopy provided conclusive evidences for the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
144
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(153 citation statements)
references
References 62 publications
6
144
0
Order By: Relevance
“…PMSO was reported to be converted to corresponding PMSO 2 via a unique oxygen atom transfer route, differing markedly from radical-mediated routes. 23,56,57 As expected, by using PMSO as the chemical probe, significant generation of PMSO 2 was detected in the PAA/CCN4 process. The conversion rate was approximately 100%, confirming that the Co(IV) species was generated in the studied process (Figure 4a).…”
Section: ■ Results and Discussionsupporting
confidence: 77%
“…PMSO was reported to be converted to corresponding PMSO 2 via a unique oxygen atom transfer route, differing markedly from radical-mediated routes. 23,56,57 As expected, by using PMSO as the chemical probe, significant generation of PMSO 2 was detected in the PAA/CCN4 process. The conversion rate was approximately 100%, confirming that the Co(IV) species was generated in the studied process (Figure 4a).…”
Section: ■ Results and Discussionsupporting
confidence: 77%
“…HA was apt to compete with organic contaminants for SO 4 •– since HA could be readily scavenged by SO 4 •– at a rate constant of 6.8 × 10 3 L·mg C –1 s –1 . In contrast, the degradation of organic contaminants by Fe­(IV) would be slightly influenced by HA because of the inert reactivity of Fe­(IV) toward HA. The degradation of phenol was mainly ascribed to Fe­(IV), whereas Fe­(IV) and SO 4 •– contributed almost equally to the degradation of estradiol (Figure d). Therefore, the presence of HA had a negligible effect on the degradation of phenol but inhibited the degradation of estradiol in the rapid oxidation stage of the Fe­(II)/PMS process.…”
Section: Resultsmentioning
confidence: 99%
“…However, specific antibacterial mechanisms of Fe­(IV) are unclear. Fe­(VI) could inactivate microbial cells via the oxidation of DNA polymerase-I. , In this process, Fe­(IV) was regarded as a key reactive intermediate, possibly because of its higher reactivity than that of Fe­(VI). , More recently, Zong et al (2021) reported a bactericidal activity of an iron–oxo species [Fe­(IV)O]. Therefore, Fe­(IV) is believed to have an antimicrobial activity, but further investigation is needed to confirm its role.…”
Section: Discussionmentioning
confidence: 99%